2011
DOI: 10.1123/jpah.8.8.1074
|View full text |Cite
|
Sign up to set email alerts
|

Adolescent Physical Activity Participation and Motivational Determinants Across Gender, Age, and Race

Abstract: There is a need to determine why PA drops-off as females get older. Findings underscore the importance of structuring activities differently to sustain interest in male and female adolescents, and highlights motives of having a healthy body image, and making PA fun to enhance participation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

7
87
0
4

Year Published

2011
2011
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 105 publications
(98 citation statements)
references
References 34 publications
7
87
0
4
Order By: Relevance
“…The CAPA assessment indicated that males were more attracted to physical activity than females. Consistent with previous research, that males valued fun as a motivation to engage in PA in comparison to females [20]. Sallis, Prochaska, and Taylor [19] found males to be more physically active than females throughout the transition from childhood to adolescence [19].…”
Section: Discussionsupporting
confidence: 76%
See 2 more Smart Citations
“…The CAPA assessment indicated that males were more attracted to physical activity than females. Consistent with previous research, that males valued fun as a motivation to engage in PA in comparison to females [20]. Sallis, Prochaska, and Taylor [19] found males to be more physically active than females throughout the transition from childhood to adolescence [19].…”
Section: Discussionsupporting
confidence: 76%
“…Males have been found to be more attracted to physical activity that allows them to exert energy and get out of breath [20]. In a study by Brustad (1993), children tended to rank fun and improving or learning new skills as the top reasons to participate in sport [24].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Por otro lado, con objeto de estudiar los comportamientos físico-deportivos y sedentarios de los adolescentes estadounidenses, la investigación de Butt et al (2011) analizó a un total de 1163 escolares (703 chicas y 460 chicos) de entre 13 y 16 años en 12 escuelas públicas y privadas del medio-oeste de los Estados Unidos, empleando para tal fin el cuestionario CAPA (Children's Attraction to Physical Activity). Sus resultados revelaron diferencias significativas en función del género (Wilks's lambda = .98 F (5, 988) = 4.04, P .001), siendo las chicas, y especialmente las más mayores, quienes participaron en menor medida en actividades físicas y con una menor intensidad que los chicos.…”
Section: Introductionunclassified
“…The link between regular physical activity (PA) and physical and psychological health has been well documented in the literature [1][2][3]. The most important benefits of regular PA include reduced prevalence of many diseases as well as decreased mortality [4][5][6][7].…”
Section: Introductionmentioning
confidence: 99%